Analysis of dynamic disturbance in blood coagulation function of patients with Coronavirus Disease 2019: A retrospective observational study. Issue 43 (23rd October 2020) - Chen, Nian; Li, Yuwen; Fan, Haozhi; Tian, Anran; Yuan, Hui; Jiang, Zhengyi; Yu, Yunxi; Ruan, Lili; Hu, Pingping; Yue, Ming; Li, Jun; Zhu, Chuanlong
Abstract : Abstract: Coronavirus Disease 2019 (COVID-19) has became a major problem affecting global health security. To assess the differences and dynamic changes of blood coagulation function in COVID-19 patients with different severity. A total of 261 COVID-19 patients from January 24 to March 25, 2020 in Huangshi, Hubei Province were enrolled. We designed a retrospective observational study. Clinical information, including age, blood routine and blood coagulation function, were collected. According to the Diagnosis and Treatment Guidelines for COVID-19 (seventh version) that issued by the National Health Committee of the People's Republic of China, patients were divided into 3 subgroups: 186 ordinary, 45 severe and 30 critical ones. We compared the differences in blood coagulation factors among groups. Average age in critical group (71.47 ± 11.48 years) was the oldest of 3 subgroups. At admission, statistically differences could be observed among ordinary, severe and critical patients in D-dimer (0.18 ± 0.33, 0.63 ± 1.13 and 1.16 ± 1.58 mg/L), fibrinogen/fibrin degradation products (FDP) (3.11 ± 5.30, 9.82 ± 23.91 and 21.94 ± 40.98 μg/ml), platelet [(169 ± 62.85), (188 ± 71.56) and (117 ± 38.31) × 10 9 /L)] and lymphocyte count [(1.18 ± 0.46), (0.82 ± 0.35) and (0.75 ± 0.39) × 10 9 /L)], respectively ( P  < .05). During hospitalization, the peak values of coagulation and valley values of blood routine were monitored. There were significant differences among ordinary, severe and critical patients in D-dimer (0.26 ± 0.46, 1.39 ± 1.51 and 2.89 ± 1.68 mg/L), FDP (3.29 ± 5.52, 23.68 ± 39.07 and 56.11 ± 49.94 μg/ml), platelet [(164 ± 55.53), (171 ± 69.96) and (84 ± 57.80) × 10 9 /L)] and lymphocyte count [(1.10 ± 0.46), (0.65 ± 0.35) and (0.55 ± 0.31) × 10 9 /L)], respectively ( P  < .001). D-dimer and FDP in the course of disease in severe/critical groups showed a first upward and then downward trend. We concluded that coagulation function indexes such as D-dimer and FDP could be served as markers to estimate COVID-19 patients condition. Close monitoring of coagulation function may be helpful for early diagnosis of severe patients and guidance of treatments.